Corporate Governance and Shareholder Litigation - Georgi Kalchev (The Icfai University Journal of Corporate Governance, 2009)
The probability for shareholder litigation is studied and how corporate governance characteristics and other factors explain it. Shareholder litigation results from failure of corporate governance. Thus a better quality of corporate governance is hypothesized to decrease the litigation probability. Corporate governance index is constructed based on principal components. It is found to be a significant predictor of shareholder litigation.
Keywords: 330; shareholder litigation; corporate governance; principal components; panel logit